189 Association of British Neurology trainees: biennial national census. Issue 6 (27th May 2022) - Ahmad, Hena; Zarkali, Angeliki; Kemp, Michael J; Banerjee, Gargi; Rees, Richard N; Shribman, Samuel; Grote, Helen; Ross Russell, Amy L
Abstract : Background: The Association of British Neurology Trainees (ABNT) conducts a biennial census of neurology trainees. This acquires data on training, education, research, out of program experiences and trainees' future plans, which are invaluable in shaping the future workforce. This is particularly important given the introduction and implementation of Shape of Training in 2022. Aim: To review trainee perspectives on neurology specialist training in 2020. Methods: Online questionnaire, designed by the ABNT committee, sent by email to all specialist neurology trainees and associate ABN members. Results: Results will be reviewed and compared with previous data by members of the ABNT committee. We hope to present these results to an audience of aspiring neurologists, trainees and consultant neurologists. Conclusion: The results of this census, in combination with those conducted in 2015 and 2017, will influence Shape of Training discussions and new curriculum design. We hope the information it provides will facili- tate communication and collaboration between the ABN, Specialty Advisory Committee, Joint Royal College of Physicians Training Board and other external bodies. This will inform future workforce planning and guide the transition through curriculum reforms. hena.ahmad2@nhs.net